The Patriots and the Food Heritage of Chile; [Los Patriotas y el Patrimonio Alimentario de Chile] - Lacoste, P (Universidad de Tarapaca, 2023)
This paper examines the link between the patriots and the food heritage of Chile, mainly during the War of Independence (1810-1824). The role of emancipation leaders and founders of the republic, particularly Bernardo O’Higgins, José de San Martín and José Miguel Carrera, is investigated. It studies the role of food, not only as a nutrient, but also in its symbolic dimension, both in the independence struggle and in the personal life of its leaders. Patriots are concerned about food such as wheat flour and specific social actors, such as artisanal fishers. There are also valuation links of foods of origin such as Chillan sausage (precursor to the local “longaniza”), Chanco cheese, Chiloé ham, Con Con corvina, lamb and some specific dishes like Valdivian. In the same way the incidence that the patriots had in the origin of the picarones in Chile is revealed. It is detected that in the first half of the 19th century, Chile had a relevant food heritage, which was visible and valued by the patriots. © 2023, Universidad de Tarapaca. All rights reserved.